2020
DOI: 10.3393/ac.2019.06.25
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation Versus Suction Alone During Laparoscopic Appendectomy for Uncomplicated Acute Appendicitis

Abstract: Original ArticleAnn Coloproctol 2020;36(1):30-34 https://doi.org/10. 3393/ac.2019.06.25 Purpose: To compare the surgical outcomes of peritoneal irrigation versus suction alone during laparoscopic appendectomy and to identify the risk factors of surgical site infection in patients with uncomplicated acute appendicitis. Methods: Data from patients with uncomplicated acute appendicitis between January 2014 and March 2016 were reviewed. We compared the irrigation and suction alone groups with regard to the foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
2
1
Order By: Relevance
“…The traditional pathophysiology of AA can be applied to patients who require surgical treatment. It has been reported that open surgery increased the incidence of surgical site inflammation [21]. However, our data did not reveal any such findings, although our study only included 33 cases of open surgery.…”
Section: Discussioncontrasting
confidence: 61%
“…The traditional pathophysiology of AA can be applied to patients who require surgical treatment. It has been reported that open surgery increased the incidence of surgical site inflammation [21]. However, our data did not reveal any such findings, although our study only included 33 cases of open surgery.…”
Section: Discussioncontrasting
confidence: 61%
“…Extensive attempts have been made to reduce the rate of such complications. For example, some studies advocate using a retrieval bag to prevent direct contact of the inflamed appendix with the incision to decrease the SSI rate ( 17 ). Others support intra-abdominal lavage to reduce the risk of intra-abdominal abscess formation, which further decreases wound infection rate ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is no evidence of the benefit of lavage over suction alone for postoperative infective complications 43 , and the insertion of a drain in the abscess cavity is controversial. In fact, there is a significantly longer operative time and a higher postoperative complication rate (surgical site infection/intra-abdominal abscess) in the irrigation group than in the suction-only group after laparoscopic appendicectomy for uncomplicated appendicitis 44 . Peritoneal and wound drains are of no use.…”
Section: Arguments For Interval Appendicectomymentioning
confidence: 94%